5 - The Exploration of Service Quality Leadership for Private Higher Education Institutions in South Africa - Steenkamp, Rigard J; Schalkwyk, Riaan Dirkse van (Journal of Higher Education in Africa, 2022)
This is a first study to explore service quality leadership within the South African private higher education (PHE) domain that emphasised the need for the development of a total quality service (TQS) framework for private higher education institutions (PHEIs) in South Africa. To address the problem, the explorative study was based on a qualitative and quantitative research approach in terms of four measuring instruments, namely (1) a literature review on general PHEI leadership perspectives related to service quality; (2) leadership perspectives by means of the Leadership Practices Inventory (LPI) assessment instrument; (3) an empirical study of service quality measured (by means of SERVQUAL) at a prominent South African PHEI; and (4) semi-structured interviews conducted with the leadership of PHEIs (fifteen principals – CEOs or top managers) from South African PHEIs. Besides the need for a TQS framework, the results indicated that service quality is a strategic performance indicator and a bigger priority for PHEIs than for public institutions. The leadership indicated a commitment to measure, manage and improve service quality on a holistic basis.